Optical properties of Cu(In1-xGax)5Se8 from ellipsometric measurements - Durán, Larissa; Castro, Jaime; Hernández, Elvis; Muñoz íngel; Naranjo, José; Durante Rincón, Carlos Alberto (Ciencia)
Spectroscopic ellipsometry measurements at room temperature were done on the system Cu(In1-xGax)5Se8. This allowed to determine the real and imaginary parts of the complex refractive index N(hn), the real and imaginary parts of the complex dielectric function e(hn), the absorption coefficient a(hn) and the reflectivity R(hn) for each studied composition. The value of the energy gap Eg for each composition was obtained from fitting the numerically obtained second derivative spectra of the experimental data e(hn), d2e(hn)/d(hn)2, to analytic critical-point line shapes. The energy gap values of CuIn5Se8 and CuGa5Se8, thus obtained, are in good agreement with those reported by other authors. The value of the high frequency dielectric constant for each composition was determined fitting the real refractive index n to the Sellmeier dispersion formula.